An improved ant algorithm for the triple matching problem - Schiff Krzysztof (Technical Transactions, 2020)
In this article a new version of the ant colony optimisation algorithm with a desirability function for the triple matching problem is described. The problem is modelled by means of two 2-dimensional arrays. The new version of the ant algorithm was compared with the previous version of the ant algorithm and tested for different values of ant algorithm parameters; the results of these tests are presented and discussed.